Four ways to get a grip on making robust decisions from workplace-based assessments - Wilkinson, Tim J (Canadian Medical Education Journal, 2022)
Synthesising the results of workplace-based assessments to inform robust decisions is seen as both important and difficult. Concerns about failing to fail the trainee not ready to proceed has drawn disproportionate attention to assessors. This paper proposes a model for a more systems-based view so that the value of the assessor’s judgement is incorporated while preserving the value and robustness of collective decision-making. Our experience has shown it can facilitate robust decisions on some of the more difficult areas, such as professionalism.